Intervention Effect of Group Reminiscence Therapy in Combination with Physical Exercise in Improving Spiritual Well-Being of the Elderly - Yujia REN; Rong TANG; Hua SUN; Xin LI (Tehran University of Medical Sciences, 2021)
Background: To explore the intervention degree and improvement effect of group reminiscence therapy in combination with physical exercise on spiritual well-being of the elderly after the outbreak of the COVID-19 epidemic. Methodology: In 2020, overall, 130 elderly people were selected from communities in Xiangtan City and Changsha City of Hunan Province, China and randomly divided into two groups, with 65 people in each group. One group was the experimental group that participated in the exercise intervention for 8 weeks as the objects of group reminiscence therapy intervention in combination with physical exercise. The other group was the control group that listened to 4 routine health lectures. Spirituality Index of Well-Being, ULS Loneliness Scale and Brief Resilience Scale were used to evaluate the effect of the intervention. Results: Before the intervention, there was no significant difference between the experimental group and the control group, but after 8 weeks of exercise intervention, the score of loneliness was lower in the experimental group than in the control group (P<0.05), the scores of spiritual well-being and resilience were significantly higher in the experimental group than in the control group (P<0.05); and the differences before and after the intervention were significantly higher in the experimental group than the control group (P<0.05). Conclusion: Group reminiscence therapy in combination with physical exercise could improve spiritual well-being and mental health of the elderly.